Logistics non-conformances managed under the aegis of Evolutionary Theory (Research, Society and Development, 2021)
The present investigation aim is to verify how the Evolutionary Theory can contribute to the improvement of the logistics processes. Methodologically, we describe it as descriptive, to comply with the objectives; as bibliographic, documental, and action research, to comply with the procedures. To approach the research problem, we used the qualitative method. To perform the research, we collected the logistics non-conformances of a consumer goods industry analyzed and managed under the aegis of Evolutionary Theory. The results found point to the relevance of the routines in learning. These routines, once improved, are reflected in solutions to the problems, due to the specialization and learning coming from the process optimization.